2014
DOI: 10.1039/c4tc00508b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optical nonlinear property of Y-type chromophores based on double-donor structures with excellent electro-optic activity

Abstract: New Y type chromophores were synthesized and the hyperpolarizability can be effectively translated into large electro-optic coefficients in poled polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 43 publications
4
106
0
Order By: Relevance
“…1, all of them undergo single electron oxidation. Most of them are donoracceptor (DA) conjugate chromophores such as the tricyanofuran amine 12 which exhibits non linear optical activity [20][21][22], amino oligoenes 1-5 [23], coumarine and perylene dyes (13,16) used so far as sensitizers for dye sensitized solar cells (DSSC) [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…1, all of them undergo single electron oxidation. Most of them are donoracceptor (DA) conjugate chromophores such as the tricyanofuran amine 12 which exhibits non linear optical activity [20][21][22], amino oligoenes 1-5 [23], coumarine and perylene dyes (13,16) used so far as sensitizers for dye sensitized solar cells (DSSC) [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The chromophores L1 even exhibit superior optical nonlinearity compared with their alkyl D-p-A counterparts (traditional chromophore FTC with the N, N-diethylaniline benzyl donor under the same condition (39 pmV À1 at 25 wt%) [21]. High r 33 value indicated that the new POZ donor can efficiently improve the electron-donating ability thus enhancing the macroscopic EO activity.…”
Section: Electro-optic Performancementioning
confidence: 97%
“…Besides, many kinds of organic chromophores based on carbazole [25], indoline [11] and other donating groups have been developed and have shown potential application for second-order NLO chromophores. The r 33 values of traditional aryl chromophores (like triphenylamine or carbazole D-p-A chromophores) remained 10e20 pm/V, which are much lower than those obtained from their alkyl D-p-A counterparts (traditional chromophore FTC achieve r 33 values of 39 pmV À1 at 25 wt%) [2,21,26]. Recent studies showed that introducing additional heteroatoms into the benzene ring moiety of donor could provide abundant opportunities for further modifications of chromophores thus influence nonlinear optical properties of chromophores [27e29].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on above point, as well as our previous work on the "double-donor chromophore" [5,9,24], we designed and synthesized three new double donor chromophores y1, y2, and y3. In our previous work, it has been shown from both theoretical and experimental analysis that the linear and nonlinear optical properties of double-donor chromophores are excellent.…”
Section: Introductionmentioning
confidence: 98%